CLOTHING PRODUCTION USING THE ZERO WASTE METHOD (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This article examines the concept and practice of Zero Waste in garment production, focusing on its environmental, technological, and creative dimensions. The Zero Waste approach aims to minimize or completely eliminate textile waste during clothing design and manufacturing. By implementing innovative pattern-making techniques and efficient material usage, designers not only reduce environmental impact but also create garments that are aesthetically appealing and structurally innovative. The study highlights the ecological significance of Zero Waste fashion, its role in fostering sustainable consumer behavior, and its potential to influence the future of the global fashion industry. Furthermore, the article explores how this method encourages designers to rethink conventional garment construction, promoting a balance between creativity and sustainability.